2014
DOI: 10.1080/02687038.2014.971099
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neural changes after a “choice” therapy for naming deficits in aphasia: preliminary findings

Abstract: Abstract:Background: Anomia, difficulty producing words, is a pervasive symptom of many individuals with aphasia. We have developed a treatment for naming deficits -the Phonological Components Analysis (PCA) protocol -that has proven efficacious for individuals with poststroke aphasia.Aims: The aim of the present investigation is to present preliminary findings exploring the potential influence of choice on our PCA treatment. Conclusion:The efficacy of PCA treatment for naming deficits is further supported. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…of a word they cannot name, guided by the use of a chart. We and others have shown that PCA treatment improves naming performance in patients who suffer from chronic non-fluent or fluent aphasia ( 7 9 ) following a left hemisphere stroke. Improved naming after standard PCA treatment has been associated with neural activation changes in left hemisphere areas (e.g., supramarginal gyrus, left inferior frontal gyrus) and to a lesser extent, in right hemisphere areas (e.g., precuneus) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 94%
“…of a word they cannot name, guided by the use of a chart. We and others have shown that PCA treatment improves naming performance in patients who suffer from chronic non-fluent or fluent aphasia ( 7 9 ) following a left hemisphere stroke. Improved naming after standard PCA treatment has been associated with neural activation changes in left hemisphere areas (e.g., supramarginal gyrus, left inferior frontal gyrus) and to a lesser extent, in right hemisphere areas (e.g., precuneus) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 94%
“…Preliminary neuroimaging data further indicate that the activation of cognitive functions, as in making an active choice, is important for successful treatment of anomia. In a study with "choice" or "no choice" conditions, all five participants demonstrated treatment effects, but only the participant from the "choice" condition showed a change in neural activation [23].…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal activation of phonological and semantic representations during naming therapy [74] might explain the fact that both semantic-and phonological-focused therapies have been found to improve naming abilities in many patients with aphasia [70,[75][76][77][78][79][80]. Such generalization was also found in our group's work [10,81]. Our specific hypotheses were as follows:…”
Section: Introductionmentioning
confidence: 57%
“…A complete presentation of the treatment results is available in the original papers [10,81]. To summarize, all treated patients demonstrated significantly improved naming of treated words post-treatment, and these gains were maintained at a follow-up assessment administered four weeks post-treatment.…”
Section: Behavioral Resultsmentioning
confidence: 96%
See 1 more Smart Citation